2006
DOI: 10.1016/j.ijsolstr.2005.05.053
|View full text |Cite
|
Sign up to set email alerts
|

A univariate approximation at most probable point for higher-order reliability analysis

Abstract: This paper presents a new univariate method employing the most probable point as the reference point for predicting failure probability of structural and mechanical systems subject to random loads, material properties, and geometry. The method involves novel decomposition at the most probable point that facilitates a univariate approximation of a general multivariate function, response surface generation of the univariate function, and Monte Carlo simulation. In addition to the effort of identifying the most p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 13 publications
0
90
0
Order By: Relevance
“…Interested readers may refer to details in the literature [14][15][16]. Experience has shown that FORM/SORM are sufficiently accurate for engineering purposes, provided that (1) the MPP is accurately identified, (2) the limit state curve/surface at the MPP is close to being linear or quadratic and (3) no multiple MPPs exist [16].…”
Section: First-and Second-order Reliability Methodsmentioning
confidence: 99%
“…Interested readers may refer to details in the literature [14][15][16]. Experience has shown that FORM/SORM are sufficiently accurate for engineering purposes, provided that (1) the MPP is accurately identified, (2) the limit state curve/surface at the MPP is close to being linear or quadratic and (3) no multiple MPPs exist [16].…”
Section: First-and Second-order Reliability Methodsmentioning
confidence: 99%
“…The estimation results are reported in Table 11. Table 11 lists the predicted failure probability of tenbar truss and the associated computational effort using FORM, several SORM, three variants of MPP-UDR, crude MCS (10 6 samples), and proposed hybrid reliability method Rahman and Wei (2006) combined with ordinary MLS and DWMLS. From Table 10, both versions of MLS predict the failure probability more accurately than FORM and all three variants of SORM.…”
Section: Example 3: a Cantilever Beammentioning
confidence: 99%
“…Using the univariate DRM, an N -dimensional performance function G(X) can be additively decomposed into the sum of one-dimensional functions at the MPP as [7,8,11]…”
Section: Drm-based Inverse Reliability Analysismentioning
confidence: 99%
“…Although the reliability analysis using SORM may be accurate, it is not easy to use as SORM requires the second-order derivatives, which are very difficult and expensive to obtain in practical engineering applications. To overcome these drawbacks and to maintain the efficiency of FORM and the accuracy of SORM, the MPP-based dimension reduction method (DRM) has been recently proposed [7][8][9][10][11]. DRM was originally proposed to approximate a multi-dimensional function using the sum of lower-dimensional functions for statistical moment estimation [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%